Pre-Hospital Delay and Its Contributing Factors in Patients with ST-Elevation Myocardial Infarction; a Cross sectional Study - Poorhosseini, Hamidreza; Saadat, Mohammad; Salarifar, Mojtaba; Mortazavi, Seyedeh Hamideh; Geraiely, Babak (Archives of Academic Emergency Medicine, 2019)
Introduction: The outcome of ST-elevation myocardial infarction (STEMI) is significantly influenced by the total tissue ischemic time. In spite of efforts for reducing the in-hospital delay by full-time provision of primary percutaneous coronary intervention (P-PCI) in the 24/7 program, pre-hospital delay still persists. As a first report in Iran, we aimed to assess the duration of pre-hospital delay and its contributing factors in STEMI patients in the P-PCI era. Methods: The present cross-sectional study evaluated 2103 STEMI patients who underwent primary PCI from 2016 to 2018. Demographic, personal and socioeconomic factors, index event characteristics, past medical history, pain onset and door times of patients were recorded and independent factors of pre-hospital delay were calculated. Results: Median (IQR) of pain to door (P2D) time was 279 (120-630) minutes. In multivariate analysis, female gender [Beta=0.064 (95%CI: 0.003-0.125); p=0.038], being uneducated [Beta=0.213 (95%CI: 0.115-0.311); p<0.001], the onset of chest pain between 00:00 to 6:00 [Beta=0.130 (95%CI: 0.058-0.202); p<0.001] or 7:00 to 12:00 [Beta=0.119 (95%CI: 0.049-0.190); p=0.001], self-transportation [Beta=0.098 (95%CI: 0.015-0.181); p=0.020] or referral from another hospital [Beta=0.253 (95%CI: 0.117-0.389); p<0.001], atypical chest pain [Beta=0.170 (95%CI: 0.048-0.293); p=0.006], history of hypertension [Beta=0.052 (95%CI: 0.002-0.102); p=0.041], and opium abuse [Beta=0.076 (95%CI: 0.007-0.146); p=0.031] were associated with a significantly higher log(P2D), while history of CABG was associated with shorter P2D. Conclusion: Our study showed that P2D is still very high in Iran and revealed the high-risk groups associated with longer P2D. Effective actions should be implemented to increase the public awareness about the symptoms of STEMI, and the importance of immediate appropriate help-seeking.